Room temperature gas and VOCs sensors based on metal oxide composites - Kilinc, Necmettin; Şişman, Orhan; Taşaltin, Cihat; Gürol, İlke (Elsevier, 2024)
The continuous operation of metal-oxide semiconductor (MOS)-based gas sensors at high temperatures results in the decreased longevity with large power consumption. In addition, when they heat up to a high temperature, this could lead to changes in the microstructure of the sensing nanomaterials, resulting in the degradation of sensing performance. For this reason, it is important to reduce the operating temperature of MOS-based gas sensors at room temperature (RT) without compromising their sensing performances. This chapter centers on the use of MO-based nanocomposites operating in room temperatures for VOC sensing. © 2024 Elsevier B.V., All rights reserved.
Keywords: MOX; MOX composites; Room temperature; Sensors; VOCs detection